Portrait d’une amazone : Asja Lacis et les privés d’enfance - Bruno Tackels (Strenae)
This study concerns the portrait of a woman, a woman as luminous in her lifetime as she was forgotten after death. It is the portrait of a great artist and refined teacher, as well as a radical communist activist, who fought for the Bolshevik revolution, which thanked her in return by sending her to the Gulag for ten years. Once recovered, she resumed her tireless theatrical work with street children, and set up a new type of theater (with the help of her friend the philosopher Walter Benjamin), which still has much to teach us.